An EPR-independent therapeutic strategy: Cancer cell-mediated dual-drug delivery depot for diagnostics and prevention of hepatocellular carcinoma metastasis. (January 2021) - Chen, Xiangjun; Zhang, Xiuping; Zhang, Lingyu; Zhao, Guodong; Xu, Shuai; Li, Lu; Su, Zhongmin; Liu, Rong; Wang, Chungang
Abstract: Motivated by the "self-seeding" of the cancer cells, the EPR-independent nanoparticles (NPs)-based therapeutic strategy have been explored to prevent hepatocellular carcinoma metastasis in this paper, the mechanism of anti-metastasis of the NPs was also evaluated. We firstly have established an aggressive whole-body spreading orthotopic LM3 tumour model closing to actual cases of human patients and the synthesized Trojan Horse-like amphiphilic nanobowls have been engineered with dual drugs with completely different pharmacokinetic profiles for cancer cell-mediated anti-metastasis therapy. These Trojan Horse-like nanobowls can serve as dual-drug delivery depots for site-specific pH/NIR dual-stimuli drug release with effectively suppressed primary tumor growth and metastases. Furthermore, the multi-mode UCL/MR/CT imaging is competent for providing comprehensive and valuable information for evaluating and adjusting the treatment. The employ of cancer cell-mediated anti-metastasis therapeutic strategy delivering drugs into metastatic cells to defeat tumor metastases provides directions in the fields of anti-metastasis therapy.